APAKAH TERDAPAT PENGARUH MOTIVASI BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS MELALUI SELF EFFICACY ? - Afida, Afnaril; Rukmigarsari, Ettie; Khairunnisa, Gusti Firda (Universitas Muhammadiyah Ponorogo, 2024)
This research is based on students always thinking that mathematics is a subject that is difficult to understand, thus causing students to be lazy and not have the enthusiasm to learn mathematics and think about solving mathematics problems. This results in students doing the questions as they please and not thinking when working on math problems. This research aims to determine the influence of learning motivation on mathematical critical thinking skills through the self-efficacy of class VII students at SMP Islam Ma'arif 02 Malang City in the 2023/2024 academic year. Using a quantitative approach with the observational/expost facto method, this research involved 73 class VII students of SMP Islam Ma'arif 02 Malang City, consisting of classes VII-A, VII-B, VII-D. Sampling was carried out using the cluster random sampling technique. Data was collected through questionnaires and test questions. The results of the research show that there is a direct influence of learning motivation on self-efficacy of 0.458, a direct influence of learning motivation on mathematical critical thinking skills of 0.319, a direct influence of self-efficacy on mathematical critical thinking abilities of 0.293, and an indirect influence of X1 on Y2 through Y1, namely 0.293 Ã—0.458 = 0.134.